The impact of superior roles in safety management on safety performance in SME manufacturing in Malaysia - Zulkifly, Syazwan Syah; Baharudin, Mohd Rafee; Mahadi, Muhammad Razif; Hasan, Nor Halim; Syed Ismail, Sharifah Norkhadijah (Sage Publications India, 2021)
Small and medium entrepreneurship (SMEs) is the backbone of countries’ development. Over the years, there have been a large percentage of workplace injuries by SMEs in Malaysia, including financial and other SMEs’ constraints, which inform of inexpensive approach, thus requiring effective approaches to boost their safety performance. SME is unique in terms of characteristics, such as flat organizational structure. Thus, the owner-managers and the supervisors’ safety management, respectively, are proposed to impact the safety performance. This signals the need to examine how owner-managers and supervisors’ safety management practices improve occupational safety performance in SME manufacturing companies. Grounded on the Theories of Accident Causation, the present study applied a research model examining the relationship between owner-manager safety management practices (safety concern, safety policy and safety motivation) and safety management of supervisors, and the overall safety performance in Malaysia’s SME manufacturing. The questionnaires were distributed to the production workers in SME manufacturing firms in Selangor, Malaysia. A total of 165 production workers participated in the study. The data collected were analysed using partial least squares structural equation modelling. Based on the analysis, the study revealed that safety concern, safety policy and safety motivation, each, have a meaningful relationship with safety performance, while the supervisor’s safety management did not significantly affect safety performance. Our results extend previous research by highlighting the importance of owner-manager safety management practices in driving safety performance and indicating how each dimension of safety management practices either enhances or inhibits safety performance. The present study is the first empirical research investigating the relationship between manager and supervisor’s safety management and safety performance in the SME manufacturing setting.